f(1/2)=-6, x = 1/2, y = -6
f(4)=-3, x = 4, y = -3
and here, we'll do the same as well
[tex]\bf \begin{array}{ccccccccc}
&&x_1&&y_1&&x_2&&y_2\\
% (a,b)
&&(~ \frac{1}{2} &,& -6~)
% (c,d)
&&(~ 4 &,& -3~)
\end{array}
\\\\\\
% slope = m
slope = m\implies
\cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{-3-(-6)}{4-\frac{1}{2}}\implies \cfrac{-3+6}{4-\frac{1}{2}}
\\\\\\
\cfrac{\quad 3\quad }{\frac{7}{2}}\implies \cfrac{3}{1}\cdot \cfrac{2}{7}\implies \cfrac{6}{7}[/tex]
[tex]\bf \stackrel{\textit{point-slope form}}{y- y_1= m(x- x_1)}\implies y-(-6)=\cfrac{6}{7}\left(x-\cfrac{1}{2} \right)
\\\\\\
y+6=\cfrac{6}{7}x-\cfrac{3}{7}\implies y=\cfrac{6}{7}x-\cfrac{3}{7}-6\implies y=\cfrac{6}{7}x-\cfrac{45}{7}[/tex]